Antiracistiske protester i sport-spectacles: Fra knyttede næver ved OL i Mexico 1968 til knælende ben ved EM-fodbold 2021 - Haas, Claus (K&K - Kultur og Klasse, 2022)
As two Afro-American sprinters, Tommie Smith and John Carlos, were staged to receive the gold and bronze medals at the Olympic Games in Mexico 1968, they transformed the victory ceremony, one of the most well-known rituals in global sport – og popular culture, into an anti-racist protest. The image of Smith and Carlos at the victory stand went around the world. In this article, the writer interrogates, why this more than 50-year-old image functions as an image with iconic appeal also today. First, this is carried out, by positioning the issue within a social constructivist theory of culture, and a theory of the concept sports-spectacle. Secondly, by taking a closer look at the signifying rituals and symbols, ingrained in the ideological hyper-structure of the Olympic Games. Thirdly, by showing how the meaning of Smith and Carlos’ protest has been revitalized in the aftermath of the NFL quarterback Colins Kaepernicks kneeling protest in 2016, strikingly enough, also among Danish athletes and within Danish public debate. The conclusion is that by closer look, the seemingly consensus about the iconic status of the image of Smith and Carlos is precarious and conflictual, mobilizing both counter protest and polarization. Not least due to the fact that sport-spectacles to an increasing degree are enmeshed in the prevailing dynamics and conflicts concerning ‘race’ and identity formation in liberal democracies in general.